Identification of HOXA1 as a Novel Biomarker in Prognosis of Head and Neck Squamous Cell Carcinoma - Li, Hui; Wang, Xiaomin; Zhang, Mingjie; Wang, Mengjun; Zhang, Junjie; Ma, Shiyin (Frontiers in Molecular Biosciences, 2021)
Hox genes, a highly conserved homolog in most animals, play vital functions in cell development and organ formation. In recent years, researchers have discovered that it can act as a tumor regulator, and its members can participate in tumorigenesis by regulating receptor signaling, cell differentiation, apoptosis, migration, EMT, and angiogenesis. Hox genes and which major members play a vital role in the progress of head and neck squamous cell carcinoma (HNSCC) is still unclear. After analyzing the expression differences and prognostic value of all Hox genes through the TCGA-HNSC database, we use histochemistry stains in 52 pairs of HNSCC slices to verify the expression level of the key member-HOXA1. In correlation analysis, we found that high HOXA1 expression is related to poor pathological grade (p=0.0077), advanced T stage (p=0.021) and perineural invasion (PNI) (p=0.0019). Furthermore, we used Cox univariate and multivariate regression analysis to confirm the independent predictive power of HOXA1 expression. To explore the underlying mechanisms behind HOXA1, we ran GSVA and GSEA and found fourteen mutual signaling pathways, including neuroprotein secretion and transport, tumor-associated signaling pathways, cell adhere junction and metabolic reprogramming. Finally, we found that the high expression of HOXA1 is significantly related to the decrease of CD8+ T cell infiltration and the decline of DNA methylation level. Our findings demonstrated that HOXA1, as a notable member of the HOX family, maybe an independent prognostic indicator in HNSCC.